2022
DOI: 10.15295/bmij.v10i2.2014
|View full text |Cite
|
Sign up to set email alerts
|

İçsel pazarlamanın yaratıcı çalışan performansı üzerindeki etkisinde narsist liderliğin rolü

Abstract: Bu çalışmanın amacı, içsel pazarlama uygulamalarının yaratıcı çalışan performansına etkisini ve bu etkileşimde narsist liderliğin rolünü araştırmaktır. Bu kapsamda içsel pazarlama uygulamaların yoğun bir şeklide uygulandığı otel, restoran ve cafe (HORECA) çalışanlarıyla anket çalışması gerçekleştirilmiştir. Analiz sonuçlarına göre içsel pazarlama uygulamalarının yaratıcı çalışan performansını pozitif yönde etkilediği, içsel pazarlama uygulamalarının narsist liderlik üzerinde negatif yönlü bir etkisinin olduğu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…As such, job security enhances the commitment and loyalty of employees towards their organizations (Bhuian and Islam, 1996), leading to employees becoming service quality conscious (Heibutzki, 2013). Kaynak (2022) in his study on how job security affects service quality found a strong and positive correlation between the two variables.…”
Section: )mentioning
confidence: 96%
See 2 more Smart Citations
“…As such, job security enhances the commitment and loyalty of employees towards their organizations (Bhuian and Islam, 1996), leading to employees becoming service quality conscious (Heibutzki, 2013). Kaynak (2022) in his study on how job security affects service quality found a strong and positive correlation between the two variables.…”
Section: )mentioning
confidence: 96%
“…Organisational culture outlines the traditions, opinions, standards, norms and behaviours shared collectively by members of a specific organisation (Kaynak, 2022). It is the firm members' shared perception that binds them together (Waagner, 2005).…”
Section: Organisational Culturementioning
confidence: 99%
See 1 more Smart Citation